In Hannover. Original photo by Atelier Friedrich Wunder, BG A9/340. Imprint on the back: Jul. Motteler, Gabelsbergerstrasse 1, Ecke Dresdenerstrasse, Leipzig-R
In Hannover. Original photo by Atelier Friedrich Wunder, BG A9/340. Imprint on the back: Jul. Motteler, Gabelsbergerstrasse 1, Ecke Dresdenerstrasse, Leipzig-R.